Understanding the Mechanism of Social Attachment Role in Social Media: A Qualitative Analysis - Yang, MaoSheng; Zhang, WenSong; Ruangkanjanases, Athapol; Zhang, Yue (Frontiers in Psychology, 2021)
Qualitative research method was used to explore the formation and development of the attach-ment relationship between users and social media in the process of using social media. Based on the attachment theory, this study selected three representative social media platforms, TikTok, WeChat and MicroBlog, as theoretical samples, and adopted NVivo12.0 to root, theorize and con-struct the original data. Research shows that users are stimulated by co-creation value to stimu-late changes in their psychological needs and self-expression, leading to the formation of social attachment. Among them, user participation is a prerequisite for driving the occurrence of co-creation value, creating a continuous use scenario for the attachment relationship between in-dividuals and social media. Further, psychological needs and self-expression play mediating roles between co-creation of value and social attachment, and promote the occurrence of personal belonging to software platforms. The findings of this research better our understandings about the mechanism of developing social attachment from continuous use of social media and offer prac-tical implications for commercial uses of social media platforms.